Vehicle highway automation - Challa, Dinesh Kumar (Kansas State University, 2009)
Vehicle Highway Automation has been studied for several years but a practical system has not been possible because of technology limitations. New advances in sensing and communication technology have now brought a realistic system within reach. This paper proposes a Co-Operative Vehicle Highway Automation System for automating traffic information gathering and decision making in a vehicle on a highway which is cost effective and near to real life implementation. Co-Operative Vehicle-Highway Automation System is the system which is implemented by technology on-board a vehicle and also on the intelligent infrastructure technology along a highway. Vehicle Automation, Collision Prevention and Avoidance, Route Guidance, Highway Information System, Vehicle tracking, and Traffic surveillance are some applications which can be implemented in the Co-Operative Vehicle-Highway Automation System. Implementing Vehicle Highway Automation System will provide an ameliorated level of road transportation. The possible benefits to society and individuals are many in terms of time, safety, comfort and overall travel quality.
Keywords: Vehicle; Highway; Automation; Co-Operative; VHAS; Test bed; Computer Science (0984); Engineering, Electronics and Electrical (0544); Information Science (0723)